Bank efficiency and economic growth: an empirical analysis of the economies of the East African Community (EAC) countries - Kessy, Pantaleo J., author; Phillips, Ronnie, advisor; Jianakoplos, Nancy, committee member; Mushinski, David, committee member; Johnson, Richard D., committee member; Shaffer, Sherrill, committee member (Colorado State University. Libraries, 2007)
Following the relatively poor economic performance experienced by Sub-Sahara African countries during 1970s and 80s, many of these nations have increasingly relied on the private sector and market signals to direct the allocation of resources. However, a private sector -led growth strategy has little chance of success unless effective and sustainable support is forthcoming from the financial sector. The degree to which the private sector contributes to economic growth will depend inter alia on the extent to which the sector can gain access to crucial financial services, such as credit, payment system and risk management services. Efficient financial systems are, therefore, necessary if greater reliance is to be placed on voluntary, market-based decision-making systems. Financial intermediaries direct resources to their most efficient uses by evaluating alternative investments and monitoring the activities of borrowers. However, despite of the growing importance of the empirical studies on finance-growth nexus, the relationship between financial sector and economic growth in Sub-Sahara African countries has been largely ignored in the available empirical literature. In this dissertation, we analyse the link between financial sector and economic growth using a fixed-effects model and balanced panel data from three East African countries, namely, Tanzania, Kenya and Uganda, during the period 1994 - 2005. We concentrate on banking sectors as they typically dominate financial intermediation in these countries. We consider both the qualitative and quantitative aspects of the banking sectors and measure the qualitative development in the sectors with the commercial banks' efficiency. As in many earlier studies, the quantitative development of banking sectors is measured by the amount of bank credit allocated to the private sector as a share of GDP. We first estimate bank efficiency in the three countries using Data Envelopment Analysis (DEA) model, and compare how the efficiency scores vary across the countries and overtime. We then use the efficiency scores to measure the importance of a well-functioning financial system to the country's economic growth. We also investigate two potential transmission mechanisms through which the financial sector can affect economic growth. The two hypothesized transmission mechanisms are through improved capital productivity and through increased volume of savings. The general hypothesis of this dissertation is that banks are essential for economic growth, because they perform the function of allocating financial resources by selecting and monitoring of entrepreneurs. The empirical analysis of the effects of the financial system efficiency on the economic growth is based on an equation relating GDP growth to bank efficiency scores and credit to the private sector as explanatory variables, while controlling for other factors. The empirical results of the study are consistent with the above hypothesis, as the bank efficiency variable is found to be positive and statistically significant for all specifications considered. The coefficient of the commercial banks' credit to the private sector is also statistically significant with the expected positive sign, suggesting that the credit allocated to the private sector by commercial banks has a positive impact on economic growth. To examine the two hypothesized channels of transmission, we test whether commercial banks efficiency variable has positive effects on the average productivity of capital and level of savings on one hand, and on the other hand we test whether these intermediate variables have positive effects on GDP growth. The empirical results confirm that commercial banks' efficiency is positively associated with both the average capital productivity and level of savings. In addition, the results suggest that these intermediate variables are positively and statistically related to GDP growth. In a nutshell, the empirical findings of this study point out to the existence of an independent effects exerted by financial system efficiency on real growth and that financial system efficiency affects real sector mainly through capital productivity improvement and an increase in the level of savings.
Keywords: finance; efficiency; studies; African literature; research; trends; politics; causality; population growth; data envelopment analysis; competition; hypotheses; variables; copyright